A novel methodology for determining creep crack initiation and growth properties using FEM with notched small punch specimens. (December 2021) - Li, Yingzhi; Dymacek, Petr; Hurst, Roger; Stevens, Paul
Highlights: A 3D FEM model has been created to calculate stress intensity factor K and limit load PL . Following BS 7910, the C *-integral can be derived for the through wall notched specimen. The C*-integral shows linear relation with the creep initiation time ti in a double logarithmic coordinate. The relation between C*-integral and the creep crack rate a ̇ appears to follow the same tendency. Material constants on CCI and CCG can be derived according to the power law using least square fitting. Abstract: Determination of material properties on creep crack initiation (CCI) and creep crack growth (CCG) using small punch tests is still a virgin field to be exploited. Spanish and Czech researchers have carried out pioneering work and put forward an approach to correlate the notched specimen with the standard CT specimen. The advantage is that, the formulas of C *-integral for CT specimen are available and can be used directly. However, building a big data pool with both SP and CT tests within the creep region is a daunting task and hence it is worthwhile to derive C *-integral formulas for notched specimens themselves. The research is novel in that it proposes a methodology to derive the key parameter C*-integral for notched small punch specimens directly without supporting known CT tests. A 3D finite element model (FEM) for through-wall notched specimen with different crack lengths is build, and a general formulas for stress intensity factor (SIF) K, and limit load PL are obtained to calculate C *-integral for notched specimen. Experiments on notched specimens are carried out for stainless steel Sanicro 25 at temperature 700 °C. By using general formulas derived in this study, the key parameter C*-integral is obtained. The relation between C*-integral and the creep initiation time ti can be drawn as a straight line in a double logarithmic coordinate. The relation between C*-integral and the creep crack rate a ̇ appears to follow the same tendency. Material constants for CCI and CCG can be derived according to the power law using least square fitting. The proposed method is not fully developed and further validating experiments will be necessary to complete the research.